2014
DOI: 10.4276/030802214x14071472109833
|View full text |Cite
|
Sign up to set email alerts
|

The circumstances and impact of injuries on adults with learning disabilities

Abstract: Introduction: People with learning disabilities experience higher rates of injury compared to the general population, but little is known about the circumstances and perceived impact of these injuries on people with learning disabilities themselves.Method: Content analysis was conducted from interviews with 113 adults with learning disabilities who had at least one injury in a 12-month period. Qualitative interviews were conducted with ten adults with learning disabilities (and their carers where appropriate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Occupational therapists also have a key role to play in addressing home and community environment issues in injury and fall prevention for people with intellectual disabilities (Finlayson et al . ), and 18 (36%) of the clients with intellectual disabilities included in this evaluation have visual impairments. This multifactorial approach is in accordance with the most recent NICE guidelines (2013) for falls prevention, which recommend strength and balance training, environmental assessment and intervention, vision assessment and referral, and medication review (National Institute for Health & Care Excellence (NICE) ).…”
Section: Findings and Clinical Implicationsmentioning
confidence: 99%
“…Occupational therapists also have a key role to play in addressing home and community environment issues in injury and fall prevention for people with intellectual disabilities (Finlayson et al . ), and 18 (36%) of the clients with intellectual disabilities included in this evaluation have visual impairments. This multifactorial approach is in accordance with the most recent NICE guidelines (2013) for falls prevention, which recommend strength and balance training, environmental assessment and intervention, vision assessment and referral, and medication review (National Institute for Health & Care Excellence (NICE) ).…”
Section: Findings and Clinical Implicationsmentioning
confidence: 99%
“…Cox, Clemson, Stancliffe, Durvasula, and Sherrington (2010) found incidence levels of falls involving people with intellectual disability at 34% across a 12month time span and with a mean of 7.21 per person. Finlayson et al (2014) found 22.5% of their sample (205 participants) falling more than once within a 12-month period. A 12.3% fall rate was found in comparison with 4.3% in the general population within the same study.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, people with intellectual disabilities sustain more injuries, falls and accidents than the general population (Finlayson, 2011; Finlayson et al., 2010; Finlayson et al., 2014). Fractures may occur from a low impact injury if a person has osteoporosis and this places people with intellectual disabilities at an increased risk of injury following a fall (Cox et al., 2010).…”
Section: Introductionmentioning
confidence: 99%